Effect of inlet geometry and Reynolds number on turbine blade leading edge cooling employing jet impingement - Irfan Ahmad Sheikh; Emad Elnajjar; Mahmoud Elgendi (Case Studies in Thermal Engineering)
An adapter is often required at the entrance of the cooling channel for ease of installation, alignment, leakproof connection, quick removal, or a manufacturing requirement. The present study investigates the effect of the inlet adapter at jet Reynolds numbers (Rej) of 1.047 × 104 and 1.047 × 105 on the leading-edge surface cooling. Two inlets, a rectangular inlet (without adapter) and a circular inlet (with adapter), have been investigated. The inlet adapter accelerates the flow into the cooling channel, and only 4–5 % mass flowrate enters jet 1, and 12–13 % enters jet 2 for both Rej. At Rej = 1.047 × 104, the inlet adapter increases the maximum temperature on the leading edge by 7 % from 339.5 K to 364 K. The adapter decreases the maximum and average Nusselt numbers (Nu) by 1.6 % and 1 %, respectively. With an adapter, uneven cooling causes a wide range of Nu on the leading edge, whereas, without an adapter, the inlet improves the flow distribution. In all cases, the observed secondary peaks of Nu are mainly caused by the flow interactions of adjacent jets. Generally, the adapter deteriorates the cooling, and these findings can guide the design and operation of turbine blades in high-temperature environments.